Post-traumatic para-ureteral urinoma (uriniferous pseudocyst) in a cat - Bacon, N. J.; Anderson, D. M.; Baines, E. A.; White, R. A. S. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
A para-ureteral urinoma was diagnosed in a one year old domestic longhaired cat presented with signs of lethargy and abdominal distension three weeks after a road traffic accident. The urinoma was caused by chronic low-grade extravasation of urine from the left ureter into the retroperitoneal space, resulting in cellulitis producing a thick fibrous capsule around the urine. Left sided ureteronephrectomy with capsular resection and omentalisation was curative.
Keywords: Urinoma; uriniferous pseudocyst; omentum; ureter